Analysis of trends in research on internationalization and production chains in the pork sector - Guardiola Esmeral, Alejandra; Lozano Arias, Cielo Tatiana; Villamil, Indira Catalina (Revista Venezolana de Gerencia, 2024)
The pig sector has shown sustained growth in the last thirteen years in Latin America, which is why it is of special importance for these economies. This article explores trends in research on internationalization and production chains in the pig sector. For this purpose, a network analysis of keyword co-occurrences was developed, which allowed visualizing the state of development of research in the field. Four clusters or thematic groups were identified that summarize the areas addressed in the research on internationalization and production chains in the pig sector: pig industry market, supply chain management and animal welfare, sustainable development in the pig industry and human welfare in the pig industry.